Nano Tips For Building Strong Asking Skills with Tatiana Kolovou. - Kolovou, Tatiana (linkedin.com, 2024)
Get quick, bite-sized tips on building strong asking skills to grow your career. Each video is less than two minutes long, so you can make learning fit into even your busiest days.